Inhibiting Factors of Health Services Puskesmas Auxiliary (Pustu) in Tobil Village, Togean District, Tojo Una-Una Regency - Magfira; Rukiyah Nggili; Moh Abubakar Talalu (International Journal of Sustainable Applied Sciences, 2023)
The purpose of this study is to determine the inhibiting factors of health services of auxiliary health centers (pustu) in Tobil Village, Togean District, Tojo una-Una Regency. This research method is Descriptive qualitative. Location This research was conducted at the Tobil Village Sub-Health Center, Togean District, Tojo Una-una Regency. The results showed that the inhibiting factors of health services of the Auxiliary Health Center (pustu) in Tobil Village, Togean District, Tojo Una-una Regency. Which is seen from the factor of facilities hindering or inadequate and human resources (medical personnel) hindering because medical personnel are still lacking. This resulted in less than optimal health services provided by the auxiliary puskesmas (pustu) Tobil Village, Togean District, Tojo Una-una Regency.Auxiliary Puskesmas (pustu) In Tobil Village, Togean District, Tojo Una-una Regency, that there is still a lack of government budget for auxiliary puskesmas (pustu). So this is what hampers the health services of the auxiliary puskesmas (pustu) in Tobil Village.